EXPERIENCING GOOGLE APPLICATIONS IN LEARNING BASIC STRUCTURE FOR EFL UNDERGRADUATES DURING COVID-19 - Supeno, Supeno; Rosyada, Amrina (Premise: Journal of English Education and Applied Linguistics, 2024)
During COVID-19, learning through Google Applications has become the first option to enable students, teachers, and lecturers to discuss lessons more easily. It only needs one Google account, and all applications can be utilized and explored. Various research has been conducted on that issue. However, few studies have focused on basic structure learning in higher education. Therefore, it is interesting to discover the Google applications emphasizing and their influence on learning English for Indonesian undergraduates. In particular, the research highlighted the utilization of Google Classroom, Google Meet, and Google Form in conducting the Basic Structure course for the 2nd-semester students of the English education program. The sample seized 40 students of the Basic Structure course and administered an explanatory sequential mixed-method design with descriptive and narrative analyses. Through English structure assignments and questionnaires, the research emphasized Google Applications, which supports students in achieving the best output and experiencing a different learning atmosphere. The results revealed that fifty per cent of the students indicated increasing achievement from the first to the second cycle, while forty-five percent indicated the opposite. The findings bring benefits in decreasing learning obstacles and obtaining alternatives to different free online applications.